Synergetic effect of co-pyrolysis of sewage sludge and lignin on biochar production and adsorption of methylene blue. (15th September 2022) - Dai, Qianjin; Liu, Qiang; Zhang, Xueyang; Cao, Lingyu; Hu, Bin; Shao, Jian; Ding, Fangjun; Guo, Xinsong; Gao, Bin
Graphical abstract: Highlights: Co-pyrolysis of SS and lignin promoted the decomposition and reduced the reaction temperature. The synergetic effect was caused by the endothermic reaction at around 750 ℃. The synergy effect of SS and lignin enhanced MB adsorption on the biochar. Function groups promote the chemical adsorption of MB on biochar produced at 400 ℃. Developed pore structure of biochar produced at 800 ℃ contributes the MB adsorption. Abstract: Much attention has been drawn to co-pyrolysis of sewage sludge (SS) and biomass, to obtain high-quality biochar by combining the favorable properties of both feedstocks. In our study, pyrolysis of SS, lignin and their mixtures (weight ratio of 50%) were carried out in a fixed bed reactor and thermogravimetric analyzer/differential scanning calorimetry (TGA/DSC). The synergy of feedstocks during co-pyrolysis at 400 ℃, 600 ℃ and 800 ℃ was investigated. The experiments were designed using response surface methodology (RSM) to investigate the influence of temperature, retention time and doping ratio on the biochar yields and their adsorption capacity of methylene blue (MB). From the TG results, decomposition of the mixture was promoted by the synergetic effect, and the reaction temperature was reduced from 741 ℃ to 688 ℃. DSC curves proved the synergetic reaction being endothermic around 750 ℃. The biochar yields varied between 0.46 and 0.75, while the MB adsorption capacity varied between 3.06 and 38.56 mg g −1 . The MB adsorption capacity was improved by the synergy effect. The excellent MB adsorption property of biochar was attributed to abundant function groups produced at 400 ℃ (OH, CH, and C = O) and elevated specific surface areas at 800 ℃ (33.59 m 2 g −1 ).